Cataract surgery in the small eye. Issue 11 (November 2015) - Hoffman, Richard S.; Vasavada, Abhay R.; Allen, Quentin B.; Snyder, Michael E.; Devgan, Uday; Braga‐Mele, Rosa
Abstract : N/A: The surgical management of cataract in the small eye presents the ophthalmic surgeon with numerous challenges. An understanding of the anatomic classification in addition to a thorough preoperative assessment will help individualize each case and enable the surgeon to better prepare for the obstacles that might be encountered during surgery. Small eyes are especially challenging in terms of intraocular lens (IOL) calculations and possible current limitations of available IOL powers, which could necessitate alternative means of achieving emmetropia. Surgical strategies for minimizing complications and maximizing good outcomes can be developed from knowledge of the anatomic differences between various small‐eye conditions and the pathologies that may be associated with each. A thorough understanding of the challenges inherent in these cases and the management of intraoperative and postoperative complications will ensure that surgeons approaching the correction of these eyes will achieve the best possible surgical results. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.